The fiery trial : Abraham Lincoln and American slavery - Foner, Eric (W. W. Norton & Co., 2010)
In a landmark work of deep scholarship and insight, Foner gives us a life of Lincoln as it intertwined with slavery, the defining issue of the time and the tragic hallmark of American history. The author demonstrates how Lincoln navigated a dynamic political landscape deftly, moving in measured steps, often on a path forged by abolitionists and radicals in his party, and that Lincoln's greatness lay in his capacity for moral and political growth.